HISTORIOGRAPHY OF THE RESEARCH OF PATRIOTIC EDUCATION IN SCHOOLS OF UKRAINE IN THE SECOND HALF OF THE 20th – EARLY 21st CENTURY - Vitalii Y. Kulchytskyi (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article analyzes scientific works devoted to the traditions of patriotic education in Ukrainian schools of the second half of the 20th – early 21st centuries. The leading tendencies of this process are determined on the basis of studying the publications in the press of that time, manuals and monographs of scientists-teachers. The conducted logical-historical analysis of the scientific problem gave grounds to state that patriotic education in Ukrainian schools in the second half of the 20th – early 21st centuries has not been the subject of a separate comprehensive research. Despite the interest of scientists in some issues of retrospective experience of patriotic education in the schools of Ukraine in the second half of the 20th – early 21st centuries, in scientific research on this issue within these chronological limits either highlighted some aspects of organizational nature or conducted extensive research on the theory and practice of educational work. The analyzed scientific works on the traditions of patriotic education in Ukraine give grounds to conclude that there is no comprehensive systematic study of the theory and practice of patriotic education in Ukrainian schools during the second half of the 20th – early 21st centuries. The analysis of these works suggests that the formation of a new man was considered by the classics of Marxism-Leninism as one of the main tasks of building a new society, and international and patriotic education was an important component of this process. It was found that the scientific works of the Soviet period, devoted to the educational process in general and patriotic education in particular, are important because they contain significant factual material and allow to characterize the socio-political and pedagogical contexts of the problem. At the same time, the expressed ideas are distinguished by bias, connection with Marxist-Leninist ideology, lack of objective assessment of pre-Soviet pedagogy and foreign pedagogical theory and practice, as well as the state and prospects of patriotic education in the Soviet state. The historiographical analysis made it possible to substantiate the theoretical and methodological principles of research (educational concepts, directions, types and principles of patriotic education, features of the organization and methods of its implementation in schools of Ukraine). It was found that the content, forms and methods of patriotic education of students have undergone transformations under the influence of socio-political, cultural and socio-pedagogical factors. The conducted research does not exhaust all aspects of the researched problem and testifies to the necessity of further elaboration of the issue of patriotic education of Ukrainian schoolchildren in the period of independence.